Mutation rates for 20 STR loci in a population from São Paulo state, Southeast, Brazil - Martinez, Juliana [UNESP] (2017)
Short tandem repeats (STRs) are genetic markers largely employed in forensic analysis and paternity investigation cases. When an inconsistency between the parent and child is considered as a possible mutation, the mutation rate should be incorporated into paternity index calculations to give a robust result and to reduce the chance of misinterpretation. The aim of this study was to estimate the mutation rates of 20 autosomal STRs loci used for paternity tests. In these loci we analysed 29,831 parent-child allelic transfers from 929 duo or trio paternity tests carried out during 2012?2016 from São Paulo State, Brazil. We identified 35 mutations in 16 loci, and they were more frequent in the paternal germline compared to the maternal germline. The loci with the highest rate were vWA and FGA and the ones with the lowest rate were PENTA E, PENTA D, D21S11, D7S820 and D6S1043. We did not identified any mutation in D2S1338, TH01, TPOX and D16S539 loci. All mutations consisted of losses or gains of one repeat unit. Mutation rates found in the São Paulo population have peculiarities, which justifies the use of regional databases in laboratories.